Application of Biomaterials and Inkjet Printing to Develop Bacterial Culture System - Tithimanan Srimongkon; Shusaku Mandai; Toshiharu Enomae (Advances in Materials Science and Engineering)
We created an automated bioassay system based on inkjet printing. Compared to conventional manual bacterial culture systems our printing approach improves the quality as well as the processing speed. A hydrophobic/hydrophilic pattern as a container supporting a culture medium was built on filter paper using a toluene solution of polystyrene for hydrophobization, followed by toluene printing to create several hydrophilic areas. As culture media we used a novel poly(vinyl alcohol) based hydrogel and a standard calcium alginate hydrogel. The poly(vinyl alcohol) hydrogel was formed by physical crosslinking poly(vinyl alcohol) with adipic acid dihydrazide solutions. The conditions of poly(vinyl alcohol) gelation were optimized for inkjet printability and the optimum mixture ratio was determined. The calcium alginate hydrogel was formed by chemical reaction between sodium alginate and CaCl2 solutions. Together with nutrients both hydrogel solutions were successfully printed on paper by means of the modified inkjet printer. The amount of each solution was demanded simply by outputting CMYK values. In the last step bacterial cells were printed on both hydrogel media. For both media we achieved a stable bacteria growth which was confirmed by microscopical imaging of the developed bacterial colonies.